2005
DOI: 10.1063/1.1955516
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio dynamics study of poly-para-phenylene vinylene

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In Table II, it is found that the major contribution to the average polymer polarizability ␣ av DFPT ͓=Tr͑␣ DFPT ͒ /3͔ is the component ␣ zz . For PPyV, the three individual principal components are very similar to those of an isolated PPV chain, 23 which may be attributed to the similarity of the structures of PPyV and PPV. Both PPyV and PPV have the property that ␣ zz ӷ ␣ yy and ␣ yy Ӎ ␣ xx .…”
Section: B Electric Field Responsementioning
confidence: 69%
See 4 more Smart Citations
“…In Table II, it is found that the major contribution to the average polymer polarizability ␣ av DFPT ͓=Tr͑␣ DFPT ͒ /3͔ is the component ␣ zz . For PPyV, the three individual principal components are very similar to those of an isolated PPV chain, 23 which may be attributed to the similarity of the structures of PPyV and PPV. Both PPyV and PPV have the property that ␣ zz ӷ ␣ yy and ␣ yy Ӎ ␣ xx .…”
Section: B Electric Field Responsementioning
confidence: 69%
“…The contributions to the charge density from different atoms can be clearly seen, and it is apparent that the polarizability is de- pendent on the atomic environment. Notable differences can be found in the first-order densities for the pristine aromatic polymers such as PPV, 23 and for PANi and PPyV, especially in the vicinity of the heteroatom nitrogen. Furthermore, according to Table II, the polarizabilities are strongly anisotropic with a relatively large response for an electric field applied along the z axis.…”
Section: B Electric Field Responsementioning
confidence: 98%
See 3 more Smart Citations